The Impact of Integrating Human and Organizational Factors on Transportation Safety: A Cross-Sector Qualitative Study - Marzena GRABOŃ-CHAŁUPCZAK (Communications of International Proceedings, 2025)
The increasing complexity of modern transportation systems reinforces the critical role of human and organizational factors (HOF) in shaping safety outcomes. While extensive research has examined human performance, safety culture, and organizational systems separately, the literature offers limited cross-sector evidence on how these dimensions interact to influence operational resilience. This gap restricts the development of integrated safety strategies applicable across diverse transport domains. This study addresses this gap by investigating the integration of HOF across four sectors—aviation, rail, road, and water transport. A qualitative research design was adopted, involving twenty semi-structured interviews with industry professionals representing operational, supervisory, and safety-management roles. Interview data were analyzed using a hybrid inductive–deductive coding approach, and factor salience was quantified using a five-point importance scale to enable cross-sector comparison. The findings show substantial variation in HOF integration across sectors. Aviation demonstrated the highest level of integration, supported by strong leadership engagement, mature reporting systems, and structured training practices. Rail and water transport exhibited moderate but uneven integration, with communication and situational awareness emerging as core strengths. In contrast, road transport revealed high human-factor salience—particularly fatigue management and decision-making—yet weaker organizational support mechanisms. Across all sectors, the most influential factors included situational awareness, teamwork and communication, leadership commitment, and non-punitive reporting systems. The study contributes a cross-sector perspective on how integrated human–organizational approaches enhance safety resilience. The findings provide actionable implications for regulators and industry leaders seeking to design targeted, sector-appropriate interventions that strengthen both human performance and organizational safety systems.
Keywords: human factors; organizational factors; qualitative research; transportation safety; resilience; leadership; automation; system integration